(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract This study examines the legal analysis of restitution for traffic accidents in Gowa Regency. The problems in this research are: (1) How is the implementation of restitution for traffic accident victims in Gowa Regency. 2) What are the constraints that cause restitution of traffic accidents in Gowa Regency. The purpose of this study is to determine: (1) To determine the implementation of restitution for traffic accident victims in Gowa Regency (2) To determine the obstacles that cause the implementation of restitution in traffic accidents in Gowa Regency. This research approach is qualitative research with the types and sources of primary data and secondary data. The population in this study was the Polres of Gowa Regency. The research samples were from several parties of the Gowa Regency police station and several communities. The data collection technique is done by using a questionnaire and documentation study. So the results of the research show that: (1) The implementation of the implementation of the right to restitution for victims of traffic accidents in Gowa Regency in Peyidik’s actions can be carried out by the process of resolving criminal cases including through ADR (Alternative Dispute Resolution), SP3 (warrant to stop investigators) and P21 (notification that the results of the investigation are complete), (2) Obstacles that lead to restitution in traffic accidents in Gowa Regency are several factors that cause it, namely legal procedure factors, law enforcement factors, legal sociology factors and economic factors. Abstrak Penelitian ini menelaah analisis hukum terhadap pemberian restitusi terhadap kecelakaan lalu-lintas di Kabupaten Gowa. Masalah dalam penelitian ini adalah: (1) Bagaimana pelaksanaan restitusi terhadap korban kecelakaan lalu lintas di Kabupaten Gowa. 2) Kendala-kendala apakah yang menyebabkan pelaksanaan restitusi kecelakaan lalu-lintas di Kabupaten Gowa. Tujuan dari penelitian ini adalah untuk mengetahui : (1) Untuk mengetahui pelaksanaan restitusi terhadap korban kecelakaan lalu lintas di kabupaten Gowa (2) Untuk mengetahui kendala yang menyebabkan pelaksanaan restitusi dalam kecelakaan lalu-lintas di Kabupaten gowa. Pendekatan penelitian ini adalah penelitian kualitatif dengan jenis dan sumber data primer dan data sekunder. Populasi dalam penelitian ini adalah polres Kabupaten Gowa. Sampel penelitian dari beberapa pihak polres Kabupaten Gowa dan beberapa masyarakat. Teknik pengumpulan data dilakukan dengan menggunakan kuisioner dan studi dokumentasi. Jadi hasil penelitian menunjukkan bahwa: (1) Implementasi pelaksanaan hak atas Restitusi terhadap korban kecelakaan lalu lintas di kabupaten Gowa pada Tindakan Peyidik dapat dilakukan dengan proses penyelesaian perkara pidana diantaranya melalui ADR (Alternative Dispute Resolution), SP3 (surat perintah penghentian peyidik) dan P21 (pemberitahuan bahwa hasil peyidikan sudah lengkap) , (2) Kendala yang menyebabkan pelaksanaan restitusi dalam kecelakaan lalu-lintas di Kabupaten Gowa, adalah beberapa faktor yang menjadi penyebab yakni faktor prosedur hukum, faktor penegak hukum, faktor sosiologi hukum dan faktor ekonomi.